5).
2 = (3x - 5) - (7 - 4x)
3x - 5 - 7 + 4x = 2
7x = 14
x = 2
---------------------------
Ответ:{2}
====================
6).
8x + 5 = 119 + (7 - 3x)
8x + 3x = 119 + 7 - 5
11x = 121
x = 121 : 11
x = 11
----------------------
Ответ: {11}
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
5.Ответ: 2
6.
Ответ: 11
Verified answer
5).
2 = (3x - 5) - (7 - 4x)
3x - 5 - 7 + 4x = 2
7x = 14
x = 2
---------------------------
Ответ:{2}
====================
6).
8x + 5 = 119 + (7 - 3x)
8x + 3x = 119 + 7 - 5
11x = 121
x = 121 : 11
x = 11
----------------------
Ответ: {11}